Civic engagement in Canada: a critical analysis of social media, care for others, and gender on volunteering and donating - Friesen, Kelsey; Kurjata, Andie (My University, 2019)
Canadians continually donate their time and money to charitable and non-profit organizations. Donating and volunteering are forms of civic engagement which many choose to engage in to improve the lives of others. Existing literature regarding civic engagement lacks focus on general volunteering and donating as opposed to event-specific volunteering and donating. We used Alberta survey data (n=1208) gathered by the University of Alberta\xe2\x80\x99s Population Research Laboratory to explore relationships between social media, care for others, and gender on civic engagement.
Presented on April 23, 2019 at Student Research Day held at MacEwan University in Edmonton, Alberta.